Adherence to Treatment Guideline Improves Patient Outcomes in a Prospective Cohort of Adults Hospitalized for Community-Acquired Pneumonia. (24th April 2020) - Lui, Grace; To, Heather K W; Lee, Nelson; Chan, Renee W Y; Li, Timothy; Wong, Rity Y K; Hui, David S C; Ip, Margaret
Abstract: Background: Understanding local epidemiology and etiologies of community-acquired pneumonia in hospitalized patients is crucial for determining the appropriateness of treatment guidelines. We aim to determine the etiologies, severity, and outcomes in adults hospitalized for community-acquired pneumonia and to study the impact of empirical antibiotic therapy on patient outcomes. Methods: We performed a prospective observational cohort study involving adults hospitalized for community-acquired pneumonia in Hong Kong. Sputum, nasopharyngeal aspirate, blood, and urine were collected for bacterial culture, molecular tests for detection of viruses and atypical pathogens, and antigen tests. Multivariable logistic regression model and Cox proportional hazard models were performed to determine independent factors associated with prolonged hospitalization and mortality. Results: From February 2017 to July 2018, 258 patients were enrolled. The median age was 73 (interquartile range, 61–80) years, 66% were male, 57% had underlying chronic illnesses, 13% had CURB-65 score ≥3, and 10% had higher 1-year mortality. Pathogens were identified in 45% of patients; 20% had viral, 15% had bacterial, and 9% had polymicrobial pneumonia. Streptococcus pneumoniae (12%), influenza virus (12%), and Mycoplasma pneumoniae (1.2%) were the most common bacterial, viral, and atypical pathogens, respectively. Nonadherence to local empirical antibiotic treatment guidelines (primarily recommending beta-lactam and doxycycline) was observed in 25% and was independently associated with prolonged hospitalization (≥7 days) and higher mortality, after adjustment for age, underlying chronic illness, and disease severity. Conclusions: Adherence to treatment guidelines was associated with shorter hospitalization and improved survival. We provided evidence for the use of doxycycline for coverage of atypical pathogens in nonsevere pneumonia. Abstract : In this prospective study involving adults hospitalized with community-acquired pneumonia, adherence to treatment guidelines was independently associated with shorter hospitalization and improved survival. Our findings provided evidence for atypical pathogen coverage with doxycycline, which was less evaluated in other cohorts.